Large-scale studies of the HphI insulin gene variable-number-of-tandem-repeats polymorphism in relation to Type 2 diabetes mellitus and insulin release. - Hansen, S; Gjesing, A; Rasmussen, S; Glümer, C; Urhammer, SA; Andersen, G; Rose, C; Drivsholm, T; Torekov, S; Jensen, D; Ekstrøm, C; Borch-Johnsen, K; et al. (2004)
AIMS/HYPOTHESIS: The class III allele of the variable-number-of-tandem-repeats polymorphism located 5' of the insulin gene (INS-VNTR) has been associated with Type 2 diabetes and altered birthweight. It has also been suggested, although inconsistently, that the class III allele plays a role in glucose-induced insulin response among NGT individuals. METHODS: We investigated the impact of the class III allele on Type 2 diabetes susceptibility in a case-control study involving 1462 Type 2 diabetic patients and 4931 NGT subjects. We also examined the potential impact of the class III allele in genotype-quantitative trait studies in three Danish study populations containing (i) 358 young healthy subjects; (ii) 4444 middle-aged NGT subjects, 490 subjects with IFG and 678 subjects with IGT; and (iii) 221 NGT subjects, of whom one parent had Type 2 diabetes. RESULTS: There was no difference in frequency of the class III allele or in genotype distribution between the 1462 Type 2 diabetic patients and the 4931 NGT subjects. Among the 358 young subjects the class III/III carriers had significantly reduced post-IVGTT acute serum insulin and C-peptide responses (p=0.04 and 0.03 respectively). However, among the 4444 middle-aged subjects we failed to demonstrate any association between the class III allele and post-OGTT serum insulin and C-peptide levels. CONCLUSIONS/INTERPRETATION: The class III allele of the INS-VNTR does not confer susceptibility to Type 2 diabetes or consistent alterations in glucose-induced insulin release in the examined populations, which consisted of Danish Caucasians.